EVALUASI PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI DESA KEBONGULO KECAMATAN MUSUK KABUPATEN BOYOLALI - Anindya Meithasari; Ari Subowo (Journal of Public Policy and Management Review, 2016)
Community-based drinking water supply and sanitation (PAMSIMAS) is government program which move in the field of drinking water and sanitation the community. PAMSIMAS aims to improve access to drinking water and decent sanitation to rural communities and peri-urban, as well as increase healthy living behavior. PAMSIMAS program to run properly it would require the participation of the community. The lack of community participation in the Kebongulo Village Musuk District Boyolali Regency, resulting in the maintenance and management of facilities are not managed by the community. Accordingly, required evaluation that looked at the impact of the program implementation PAMSIMAS on changes in patterns community of clean and healthy living behavior (PHBS) and environmental conditions which happened after PAMSIMAS program running. This research using methods descriptive qualitative research. Data in this research obtained from interviews with informants, observation and documents. The results of this study indicate that the evaluation of PAMSIMAS program in the Kebongulo Village Musuk District of Boyolali Regency, there are changes of PHBS in society, although PAMSIMAS program still has a minimal role. PAMSIMAS role in improving PHBS only until socialization stage. While the changes in environmental conditions, still has shortcomings in terms of community participation, local institutions and government commitments affecting PAMSIMAS programs in Kebongulo village.